Drip fertigation for greater yam (Dioscorea alata) and maize (Zea mays) intercropping - NEDUNCHEZHIYAN, M; BYJU, G; JATA, S K (The Indian Journal of Agricultural Sciences, 2021)
An experiment was laid out in split-plot design with three replications. Main and sub plots consisted of drip irrigation [I1- at 80% of cumulative pan evaporation (CPE) during 1-270 days after planting (DAP), I2-at 100% of CPE during 1-90 DAP + at 80% of CPE during 91-270 DAP and I3-at 100% of CPE during 1-270 DAP] and fertigation (F1-N-P2O5-K2O 100-90-100 kg/ha, F2-N-P2O5-K2O 120-90-120 kg/ha, F3-N-P2O5-K2O 140-90-140 kg/ha and F4- N-P2O5-K2O 160-90-160 kg/ha) treatments respectively. The drip irrigation treatments I1(F2) and I2(F2) saved 17.3% (690 m3/ha) and 7.8% (310 m3/ha) irrigated water over surface flood irrigation at same level of fertilizer application (N-P2O5-K2O 120-90-120 kg/ha) (check). Electricity consumption saved 104 (17.4%) and 47 (7.9%) kWh/ha by adopting drip irrigation levels I1(F2) and I2(F2), respectively over check. The system productivity with the application of N-P2O5-K2O 100-90-100 kg/ha (F1) along with drip irrigation at I2 was comparable with check which indicated a net saving of N-K2O 20-20 kg/ha. The net income from drip irrigated greater yam (Dioscorea alata L.) + maize (Zea mays L.) under I1(F2) and I2(F2) was about 9 100 and 62 100 ₹/ha higher than the crop cultivated with surface flood irrigation (check), respectively. Greater system productivity in the treatments I2F4 (31.8%) and I2F3 (29.9%) over check indicated fertilizer responsiveness under drip fertigation. Considering environmental and economical impact, the partial deficit drip irrigation and fertigation treatment I2F3 could be the best for greater yam+maize intercropping system.